Pembatasan Pergaulan Calon Suami dan Istri Pada Masa Pertunangan dalam Perspektif Sadd Al-Dzari’ah: Studi Kasus di Desa Ambat Kecamatan Tlanakan Kabupaten Pamekasan - Luluk Nur Azizah (At-Tafakur: Jurnal Ilmu Syari'ah dan Hukum, 2024)
Islam has its own ethics in social interactions and in introducing men and women, known as ta'aruf (introduction). Engagement is considered a "sign of commitment" for the woman, signifying that she should not be proposed  to by other men. This research employs a qualitative approach, using two data collection techniques: semi-structured interviews and observations. The results of the study show that the community's view on the social behavior of engaged couples in Ambat Village perceives the actions of a prospective husband frequently visiting his fiancée's home or riding together as somewhat inappropriate. The restrictions imposed by parents in Ambat Village are a form of sadd al-dzari'ah, which means that an action, although permissible in principle, may sometimes lead to harm (mafsadah), such as being alone in seclusion (khalwat), engaging in intimate acts, or other behaviors prohibited by Islamic law. The restriction of interactions between prospective husbands and wives during the engagement period falls under the category of prioritizing the prevention of harm (mafsadah) over achieving benefit (maslahah).